The Impact of Workload, Work Environment, and Job Satisfaction on Turnover Intention: Dampak Beban Kerja, Lingkungan Kerja, dan Kepuasan Kerja Terhadap Niat Berpindah Kerja - Aprilia Imaniar; Lilik Indayani (Academia Open, 2024)
This study aimed to investigate the impact of workload, work environment, and job satisfaction on turnover intention in CV. Mitra Dunia Palletindo. The study used a quantitative approach with a sample of 78 employees. The data were analyzed using multiple linear regression analysis, R2, R, F-test, t-test, and classical assumption test with SPSS version 18 for Windows. The results showed that workload, work environment, and job satisfaction had a significant effect on turnover intention. Workload had a significant effect on turnover intention, as did work environment and job satisfaction. This study implies that companies should pay attention to workload, work environment, and job satisfaction to reduce turnover intention and increase employee retention.Highlights: Turnover intention is influenced by job satisfaction, work stress, and work environment. Job satisfaction has a negative effect on turnover intention, while work stress and unsupportive work environment have a positive effect. Workload, negative emotions, lack of support, and low wages are factors that contribute to high work stress and turnover intention. Keywords: turnover intention, job satisfaction, work stress, work environment, employee retention